Implant Rehabilitation for Extremely Atrophic Maxillae (Cawood Type VI) with Le Fort I Downgrafting and Autogenous Iliac Block Grafts: A 4-year Follow-up Study - VAROL, ALTAN; ATALI, ONUR (QUINTESSENCE PUBLISHING CO INC, 2016)
Purpose: The aim of this 4-year retrospective follow-up study was to investigate treatment outcomes, including implant survival rate and marginal bone loss, in patients with maxillary Cawood type VI atrophy pattern who underwent Le Fort I downgrafting and iliac block augmentations for implant rehabilitation. Materials and Methods: Retrognathic edentulous Class III patients with severe maxillary resorption (Cawood VI) were enrolled. Reconstructive procedures performed included Le Fort I maxillary osteotomy, iliac block grafting, labial sulcoplasties, and dental implant placement. Panoramic radiographs were used to assess marginal bone loss. The Nobel Biocare Replace and GMI Frontier dental implant systems and fixed partial dentures were used for dental rehabilitation. Statistical analyses were made using NCSS 2007 statistical software, with significance set at P <.05. Results: Ten patients (six men and four women) with a mean age of 50.4 +/- 12.55 years underwent maxillary osteotomy (advancement: 9 +/- 1.4 mm; inferior repositioning: 8 +/- 1.0 mm) and iliac block sandwich grafting (posterior ilium: n = 3; anterior ilium: n = 7) from 2009 to 2015. Nine patients were treated with a two-stage protocol. The mean graft healing period was 5.9 +/- 0.73 months. A total of 98 implants were placed, 80 in maxillae and 18 in mandibles. The Nobel Biocare Replace system was used in two patients (n = 29 implants) and GMI Frontier system was used in eight patients (n = 69 implants). Implant numbers in the maxilla were: 6 implants in 2 patients, 8 implants in 6 patients, and 10 implants in 2 patients. The mean follow-up period was 47.8 +/- 3.4 months. The success rate was 93.75%, with a 6.25% fail ratio (n = 9 implants) at a follow-up of 4 years. Marginal bone resorption was 1.8 +/- 1.0 mm at the postoperative year 1 and 3.75 +/- 0.85 mm at postoperative year 4. Marginal resorption in the 8-implant group was found to be higher than that in the 6-implant group and 10-implant group at the postoperative year 1 (P =.045, P =.026, P <.05, respectively). Conclusion: Le Fort I osteotomy and simultaneous iliac block grafting (downgrafting) is a valuable option for implant rehabilitation in extremely atrophic maxillae (Cawood VI). It showed a high survival rate (93.75%) at 4 years of follow-up in this study.
Keywords: atrophy; graft; iliac; implant; Le Fort I osteotomy; maxilla; INTERPOSED BONE-GRAFTS; ENDOSSEOUS IMPLANTS; EDENTULOUS MAXILLA; ENDOSTEAL IMPLANTS; DENTAL IMPLANTS; ORAL IMPLANTS; OSTEOTOMY; RECONSTRUCTION; SURVIVAL; COMBINATION